التكامل البصري الحركي و علاقته باداء مهام الخط عند ذوي عسر الكتابة تلاميذ الصف الثالثة ابتدائي بمدارس ولاية عين صالح - ام هاني بوخريص; جيهان قريوان; مشراوي ابتسام (My University, 2023)
The current study aims to reveal the relationship between visual-motor integration and the performance of calligraphy tasks among third-year primary school students, who have an intelligence level of 90 percent or more, as well as to detect the differences between males and females in visual-motor integration. The sample of 13 students was tested, and tools were applied to collect the study data represented in the observation and interview, the intelligence test by Dr. Muhammad Jalal Sirri to detect the level of intelligence, and we used the dysgraphia test by Bouzid Saliha to ascertain whether the children suffer from dysgraphia, then the handwriting test to evaluate the level of the child’s performance . The visual-motor integration test. Then the study tools were applied in three schools in the state of Ain Saleh. The results revealed that there is a correlation between visual-motor integration and the performance of calligraphy tasks for dyslexic third primary students, and the study also found that there are statistically significant differences between the gender variable and visual-motor integration. Keywords: visual motor integration. dysgraphia Perform line tasks